The Adjustment of the Economy to Monetary Changes - Zwick, Burton (Journal of Political Economy, 1971)
In this paper, I first indicate how the contrasting views of Keynes and Irving Fisher about the relative substitution of money for bonds and for goods imply different processes of monetary adjustment and opposite responses of interest rates to changes in the monetary base. I then present estimates of an equilibrium interest rate model. These estimates, including a pair of responses of interest rates to changes in the base, are used to discriminate between the theories of Keynes and Fisher. The results suggest that both the Keynesian and Fisherian theories are necessary to analyze monetary adjustment processes.